A Defensoria Pública como instrumento de acesso à justiça - Moraes, Ana Carvalho Ferreira Bueno de (2009)
This study investigates the performance of the Public Defense institution, in the search for actual access to courts. The principle of access to courts is the purpose of this work, which analyzes its hindrances and the ways to overcome them. Accordingly, the exposition discusses the right to free legal assistance, as established by the 1988 Brazilian Federal Constitution, as well as the addressees thereof, and the way to implement it through Pro Bono Lawyers. Thus, the institution of the Public Defense is carefully studied, through the analysis of its characteristics, principles, attributions and institutional bodies; prohibitions, guarantees, prerogatives and the responsibilities of the members of the Public Defense Office, as provided for in Complementary Law No. 80/1994 and in State Laws, with especial focus on Law No. 988/2006 of the State of São Paulo, since that legal instrument presented several novelties and advancements in the performance of the institution. Besides this, the study focuses on the performance of Pro Bono Lawyers in class actions. Finally, the work discusses extrajudicial performances, with emphasis on alternative means to settle conflicts (conciliation, mediation and arbitration), to be developed by the Public Defense Office, in addition to proactive performances of the institution in the education of the rights of the needy population